POU5F1 bridges Hedgehog signaling and epithelial remodeling in COPD - Petit, Laure M. G.; Belgacemi, Randa; Mulette, Pauline; Brisebarre, Audrey; Saber Cherif, Lynda; Devilliers, Maëva A.; Hatoum, Sarah; Ancel, Julien; Delepine, Gonzague; Durlach, Anne; Polette, Myriam; Deslée, Gaëtan; et al. (Frontiers in Cell and Developmental Biology, 2025)
Airway epithelium remodeling is a hallmark of chronic obstructive pulmonary disease (COPD) pathogenesis. Hedgehog signaling is activated during airway epithelial repair to warrant proliferation and during cell differentiation to establish a fully functional epithelium with optimal mucociliary clearance. Consequently, it was found to be altered in COPD patients. Using transcriptomic analysis on air–liquid interface airway epithelial cells during differentiation upon Hedgehog pathway inhibition, we highlighted potential regulators of COPD-associated epithelial remodeling. Furthermore, the alteration of POU5F1 (OCT3/4) was validated in COPD airway epithelial cells and lung tissues. Although further investigations are required, these findings uncovered essential clues tethering respiratory epithelial cell plasticity and Hedgehog signaling.